Notable changes in geochemical and mineralogical characteristics of different phases of episyenitization: insights on the radioactive and shielding of the late phase - Taalab, Sherif A.; Zakaly, Hesham M. H.; Ivanov, V.; Alrowaily, Albandari W.; Awad, Hamdy A.; Abed, Neveen S.; Issa, Shams A. M.; Eltohamy, Amira M.; Ene, Antoaneta (Frontiers in Earth Science, 2023)
Kab Amiri granites are submitted to post-magmatic hydrothermal solutions through fracture and faults, causing several alteration processes. The most common processes are episyenitization, saussuritization, hematitization, sericitization, kaolinization, albitization, chloritization, silicification, and muscovitization. Kab Amiri granites are vuggy, with the vugs partially to completely refilled with new constituents. The least episyenitized granites have elevated amounts of Fe, P, Zr, Ni, U, Th, Ba, Y, Hf, Nb and As, which are correlated with their mobilization from biotite, k-feldspar, plagioclase and metamict zircon. These elemental changes are related the partial albitization, muscovitization, desilicification and chloritizatiom, which lead to the mobilization of these elements and forming of specific mineral association in the least altered granites such as autonite, tripiolite, columbite, Zircon and galena. On the second stage, granites were subjected to intense alteration processes by mineralizing fluids, causing wholly muscovitization of biotite and feldspar, albitization of plagioclase, carbonitization and apatitization. Many elements were mobilized from these altered minerals,